Osculatory Surfaces Extraction applied to Monitoring of Sub-marine Sand Materials. Issue 6 (2nd November 2018) - Debese, N.; Jacq, J. J.; Degrendele, K.; Roche, M.; Garlan, T.
Abstract: This work aims at providing geoscientists with a new robust shape transform that performs the estimation of a smooth submarine intra-sediment shape from Multi-Beam Echo Sounders data. This shape matches a virtual geodesic interface between mobile and immobile sand, called an osculatory surface. The transform operates through only two non-optional parameters: its scale length and the corresponding degree of the local representations. Application tests addressing different tidal sandbanks are described. Applications to the osculatory tracking of two monitoring zones over fifteen years are also included.